Molecular, biochemical and physiological characteristics associated with quality and tolerance to drought and low temperature in tea (Camellia sinensis (L) O. Kuntze) - Steyn, Joachim Marthinus (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.